TINGKAT KERACUNAN PESTISIDA ORGANOFOSFAT PADA PETANI PENYEMPROT SAYUR DI DESA LIBERIA TIMUR KABUPATEN BOLAANG MONGONDOW TIMUR TAHUN 2013 - Ika Rahmawati; Suwarja Suwarja; Steven Jacub Soenjono (Jurnal Kesehatan Lingkungan, 2014)
A class of organophosphate pesticides used by farmers to disinfect because they have the power Exterminate strong and fast and have properties that easily decompose in nature. Nevertheless pesticide compounds organophosphate poisoning in humans can cause both acute and chronic. Class of organophosphate pesticides is inhibiting the enzyme activity kolinestrase in the body. This study aims to determine the level of pesticide poisoning organophosphate class of farmers vegetable spray. This study is descriptive done by using proportional random sampling (15 respondents). The data collection is done by observation and direct interviews and measurements of blood kolinestrase respondents using Cholinestrase Test Kit. The results showed that 8 (53.3%) did not experience poisoning (normal category), 7 (46.7%) mild poisoning, and no farmers poisoned moderate and evere categories. Parmers who suffered mild poisoning are advised to take a break from all the work relating to pesticides for two weeks.